Characterization of β-Galactosidase from Lactose Utilizing Yeast Isolated from the Dairy Sample - Dahal, Bivek; Karki, Sujan; Adhikari, Nabaraj; Shrestha, Upendra Thapa (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The objective of the study was to isolate lactose positive yeasts from dairy samples collected from local markets of Kathmandu, to extract crude β-galactosidase from the lactose positive yeast and to characterize the enzyme for optimum time duration, pH, temperature, Michaelis-Menten constant (Km) and maximum activity (Vmax). Methods: Four lactose positive yeast strains were isolated from dairy samples collected from local market of Kathmandu by pour plate method. Single strain having maximum lactose positive activity was selected for the study. The mass culture of the lactose positive yeast strain was lysed by 2% Chloroform and the yeast cell lysate containing β-galactosidase (i.e. crude enzyme extract) was characterized by using ONPG (Ortho-Nitrophenyl-β-D-galactopyranoside) as substrate. ONPG is a colorless substrate for the enzyme assay which is hydrolyzed by the enzyme into yellow colored product ONP (Ortho-Nitrophenol). The concentration of product formed was monitored spectrophotometrically at 420 nm to determine the enzyme activity and to characterize the enzyme. Results: The enzyme had wide range of working temperature from 0-50ºC, with optimal temperature of 37ºC. However, greater than 50% hydrolyzing ability was maintained in the range of 14-40ºC. Optimum time of reaction was 70 min. The enzyme had maximum activity in the near neutral pH of 6.8. Michaelis-Menten constant of the enzyme was found to be 2.23 mM of ONPG and Vmax was 58.82 nmol/min/ml. Enzyme activity was 27.88 nmol/min/ml, Specific enzyme activity was 59.97 nmol/ min/mg and total enzyme activity was 3346.33 nmol/min. Conclusion: The activity over a wide range of temperature 0-50ºC with low Km value shows that the enzyme has a commercial application in clearance of lactose pollution in waste water in different environmental conditions.